2015
DOI: 10.1038/srep10961
|View full text |Cite
|
Sign up to set email alerts
|

The existence of bronchiectasis predicts worse prognosis in patients with COPD

Abstract: Bronchiectasis is prevalent in patients with COPD. The objective of this study was to assess the clinical characteristics and prognostic value of bronchiectasis in patients with COPD in China. Data from patients diagnosed with COPD at the Shanghai Pulmonary Hospital between January 2009 and December 2013 were retrospectively collected and analyzed. SPSS statistical software was used to analyze the data. Data from 896 patients with COPD were analyzed. Bronchiectasis was present in 311 patients. The isolation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 33 publications
11
75
2
5
Order By: Relevance
“…Therefore, besides medical history, typical manifestations of inactive tuberculosis on CT were also used as the diagnostic criterion of previous tuberculosis in our study. Our results showed that the prevalence of previous tuberculosis was 43% in patients with moderate–severe COPD, which was much higher than that previously reported, [2,4,11] but consistent with the findings by Allwood and coworkers. [35] Taken together, these findings suggest that previous tuberculosis of the lung may be an important cause of coexistent bronchiectasis in COPD, and previous tuberculosis should be incorporated into the assessment of COPD, particularly in tuberculosis prevalent countries.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, besides medical history, typical manifestations of inactive tuberculosis on CT were also used as the diagnostic criterion of previous tuberculosis in our study. Our results showed that the prevalence of previous tuberculosis was 43% in patients with moderate–severe COPD, which was much higher than that previously reported, [2,4,11] but consistent with the findings by Allwood and coworkers. [35] Taken together, these findings suggest that previous tuberculosis of the lung may be an important cause of coexistent bronchiectasis in COPD, and previous tuberculosis should be incorporated into the assessment of COPD, particularly in tuberculosis prevalent countries.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, there is also a high prevalence of pulmonary tuberculosis in COPD patients, [30,33,34] and tuberculosis is defined as a risk factor for COPD by GOLD. [1] A study by Mao et al [2] showed that the proportion of patients with previous lung tuberculosis defined by a medical history was 12.1% in a Chinese cohort of COPD (n = 896). However, another population survey (age ≥ 50 years, n = 8066) in China [11] demonstrated that the proportion of people with previous lung tuberculosis was 24.2% when the diagnosis was made based on the manifestation of “inactive tuberculosis” on chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bronchiectasis and COPD often coexist with a varying prevalence amongst study populations (29%‐57%) 22, 23, 24, 25. Both diseases share several pathophysiological features including increased airway inflammation, propensity for exacerbations, distortion of the architecture of the lung parenchyma and bacterial colonisation of the airways.…”
Section: Pathophysiology Of Ncfbmentioning
confidence: 99%